In Vivo Release of Tissue-Type Plasminogen Activator across the Human Forearm during Mental Stress - Jern, Christina; Selin, Lena; Jern, Sverker (Thrombosis and Haemostasis, 1994)
We have previously shown that plasma levels of endothelium-derived tissue-type plasminogen activator (t-PA) increase during mental stress. The aim of the study was to investigate in vivo release in an intact human muscle vascular bed. Eleven healthy young males (22-36 yrs) were studied at rest and during 10 min of mental stress (forced arithmetic). Net release or uptake were assessed by arterio-venous (AV) concentration gradients across the forearm of t-PA antigen and t-PA activity, and plasminogen activator inhibitor antigen type 1 (PAI-1). Forearm blood flow was measured by venous occlusion plethysmography. At rest, there was a positive AV-difference of t-PA activity across the forearm indicating a net release of t-PA activity of approximately 3.7 fmol × min−1 × 100 ml−1 (Wilcoxon’s signed rank test vs 0, p = 0.01). However, t-PA antigen showed a variable release pattern. On the average, there was a net release of 0.17 ng × min−1 × 100 ml−1 after 60 min of rest (Wilcoxon vs 0, p = 0.07). PAI-1 antigen showed net release at rest. In response to stress, forearm blood flow increased from 1.9 to 2.9 ml × min−1 × 100 ml−1 (ANOVA, p = 0.007), and net release of t-PA activity increased to 9.8 fmol × min-1 × 100 ml −1 (ANOVA, p = 0.01 compared with rest). Arterial and venous plasma t-PA levels also increased significantly during stress (ANOVA, p < 0.01). t-PA antigen showed a similar but less pronounced release pattern during stress. PAI-1 antigen was unaffected by stress. During i. a. infusion of norepinephrine (6-1,200 ng/min), forearm blood flow decreased from 2.1 till 1.0 ml × min-1 × 100 ml−1 (ANOVA, p = 0.002), while net release of t-PA activity increased from 2.7 till 10.1 fmol × min-1 × 100 ml−1 (ANOVA, p = 0.002). The study demonstrates a net release of t-PA activity across forearm tissues at rest. Net release of t-PA activity increases in response to mental stress and i. a. infusion of norepinephrine, despite disparate effects on blood flow.